Wallenda-Nmo Axis Regulates Growth via Hippo Signaling - Wang, Xianping; Liang, Hui; Xu, Wenyan; Ma, Xianjue (Frontiers in Cell and Developmental Biology, 2021)
Wallenda (Wnd) is a member of MAPKKK (mitogen-activated protein kinase kinase kinase) family, which plays important roles in regulating synaptic growth, axon regeneration, cell death, and cell migration. However, a role for Wnd in regulating proliferation remains underexplored. The Hippo signaling pathway is a master regulator of organ size control and tumorigenesis. Here we show that ectopic expression of Wnd induces overgrowth by inactivating Hippo pathway in the Drosophila wing imaginal disc. Genetically, we identify the kinase Nemo (Nmo) as an essential downstream component of Wnd in regulating Hippo activity. Moreover, both Wnd and Nmo are required for loss of polarity-induced cell proliferation and Hippo inactivation. In summary, our findings establish a Wnd-Nmo axis acting as an additional branch that regulates Hippo pathway-mediated growth in Drosophila.